Why are Small Firms Different? Managers' Views - Jonas Agell (Center for Economic Studies and ifo Institute (CESifo), 2003)
Do incentives in small organizations differ from those in large ones? This paper uses a representative survey of compensation managers to shed light on the issues. I find that (i) small establishments rely less on pecuniary incentives, and have a significantly more hostile attitude towards incentive schemes based on competition and relative rewards; (ii) large units are more vulnerable to mechanisms of efficiency wages, effects that remain even as I control for differences in monitoring ability; (iii) large units are more prone to indicate that negative reciprocity is important, and that their employees care about relative pay. I argue that these findings fit with behavioral stories of incentives and motivation, in particular those stressing group interaction effects, inequity aversion and gift exchange.
Keywords: 330; -size effect; motivation; relative pay; field-survey; matched data